The role of the pedagogue in the opinion of students of education - Wiesława Walc (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
School counselor (pedagogue) is a specialist most often employed in Polish schools. The profession was established in the school year 1973/1974, and for many years the authorities tried to clarify the list of tasks performed by its representatives. In the essay, the process of shaping the specifics of the role of professional school counselors has been taken into consideration The author analyzed the results of research on this issue, carried out among students of pedagogy. She discussed respondents' opinions about the school counselor's tasks, difficulties and barriers to their implementation, the standard of this specialist (his desired personality traits, knowledge and skills) as well as the students' willingness and readiness to work in this profession.